5(4c-1)-1=16c+2

Simplify each term.

Apply the distributive property.

5(4c)+5⋅-1-1=16c+2

Multiply 4 by 5.

20c+5⋅-1-1=16c+2

Multiply 5 by -1.

20c-5-1=16c+2

20c-5-1=16c+2

Subtract 1 from -5.

20c-6=16c+2

20c-6=16c+2

Subtract 16c from both sides of the equation.

20c-6-16c=2

Subtract 16c from 20c.

4c-6=2

4c-6=2

Add 6 to both sides of the equation.

4c=2+6

Add 2 and 6.

4c=8

4c=8

Divide each term in 4c=8 by 4.

4c4=84

Cancel the common factor of 4.

Cancel the common factor.

4c4=84

Divide c by 1.

c=84

c=84

Divide 8 by 4.

c=2

c=2

Solve for c 5(4c-1)-1=16c+2